Analysis of the Influence of E-Trust of E-Service Quality on E-Loyalty Through E-Satisfaction in Online Trading Services at PT. Midtou Aryacom Futures Semarang - Senda, Maurinus Junedi Laka; Retnawati, Berta Bekti (STIE Pelita Nusantara Semarang, 2026)
Trading is a buying and selling activity in the capital market aimed at generating substantial profit within a short period of time. This study aims to analyze the influence of e-trust and e-service quality on e-loyalty, with e-satisfaction as a mediating variable, in the online trading services of PT Midtou Aryacom Futures Semarang. A quantitative approach was employed, and data were collected through questionnaires distributed to active customers. The analysis results indicate that e-trust and e-service quality have a positive and significant effect on e-satisfaction, which in turn significantly influences e-loyalty. These findings confirm the importance of trust and electronic service quality in building customer satisfaction and loyalty in the digital era, particularly within the context of online trading.